2018
DOI: 10.1002/slct.201801260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structural Modification on the Photoelectrical Properties of the D‐A‐π‐A‐Type Dyes in DSSCs: A Computational Investigation

Abstract: The structure-activity relationships of the three DÀA-p-A type dyes (LC6, LC7 and LC8) were investigated via density functional theory (DFT) and time-dependent DFT methods. The results indicate the substitution of thiophene with benzene ring as p spacer has intensified the distortion in the structure of LC8, which will ease the aggregation of dye on the photocathode. The greatest shift of the conduction band of TiO 2 , driving force of electron injection, excited state lifetime and lowest lateral intermolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Therefore, considering the obtained results, the dyes with the best properties are TPAZ7, TPAZ4, TPAZ3, and TPAZ5. The chemical hardness received particular attention in this prediction regarding previous studies reported [5,88,89,90]. It can be recommended to synthesize and experimentally research dyes with azomethine on the π-bridge in DSSC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the obtained results, the dyes with the best properties are TPAZ7, TPAZ4, TPAZ3, and TPAZ5. The chemical hardness received particular attention in this prediction regarding previous studies reported [5,88,89,90]. It can be recommended to synthesize and experimentally research dyes with azomethine on the π-bridge in DSSC.…”
Section: Discussionmentioning
confidence: 99%
“…First, scientists construct or design molecular structures of the dye sensitizers based on reported dye sensitizers with good performance and then calculate the electronic structures and excitation properties. Next, the effectiveness of the constructed or designed dye sensitizers with different moieties can be assessed according to their calculated energy levels, LHE, and other properties. For instance, based on the organic dye sensitizer C275, couples of dye molecules were designed by varying the electron donor, electron acceptor, and conjugate bridge units, and the photovoltaic performances were evaluated according to their energy level alignment and light absorptions. …”
Section: Introductionmentioning
confidence: 99%
“…All the calculations in this work were completed by using Gaussian program suite [14]. The geometric configurations of the investigated compounds were optimized in the framework of DFT [15][16][17], with B3LYP [18][19][20][21][22][23] functional at 6-31G(d,p) basis set. For the sake of the following discussion, we have numbered the atoms in the compound 1PP.…”
Section: Introductionmentioning
confidence: 99%